A low-threshold high-index-contrast grating (HCG)-based organic VCSEL. (December 2015) - Shayesteh, Mohammad Reza; Darvish, Ghafar; Ahmadi, Vahid
Abstract: We propose a low-threshold high-index-contrast grating (HCG)-based organic vertical-cavity surface-emitting laser (OVCSEL). The device has the feasibility to apply both electrical and optical excitation. The microcavity of the laser is a hybrid photonic crystal (HPC) in which the top distributed Bragg reflector (DBR) is replaced by a sub-wavelength high-contrast-grating layer, and provides a high-quality factor. The simulated quality factor of the microcavity is shown to be as high as 282, 000. We also investigate the threshold behavior and the dynamics of the OVCSEL optically pumped with sub-picosecond pulses. Results from numerical simulation show that lasing threshold is 75 nJ/cm 2 . Highlights: We propose a low-threshold high-index-contrast grating (HCG)-based OVCSEL. The simulated quality factor of the microcavity is shown to be as high as 282, 000. We model the dynamics of the OVCSEL optically pumped with sub-picosecond pulses. Results from numerical simulation show that lasing threshold is 75 nJ/cm 2 . The optically threshold would correspond to a laser current density of 18.9 A/cm 2 .